THE IMPLEMENTATION OF REWARD AND PUNISHMENT TOWARDS STUDENT PERCEPTION IN ENGLISH LEARNING AT IKIP SILIWANGI - Dhea Widya; Yusi Amalia Sri Wantina (IKIP Siliwangi, 2019)
This Research titled THE IMPLEMENTATION OF REWARD AND PUNISHMENT TOWARD STUDENTS’ PERCEPTION IN ENGLISH LEARNING AT IKIP SILIWANGI aimed to investigate the students’perception of reward and punishment and analyze the positive effect to student. This study imployes a qualitative reseach and the strategy used in this reseach is descriptive qualitatiave. This research took place at English Education Department Program IKIP SILIWANGI by involving interview college students at two classes randomly. The finding of this research is students’perception of reward and punishment. the students who proper to get a punishment when the students do not do the assignment, coming late etc. and the students who proper to get the reward when the students can answer the questions and also get additionl score. they can get B score for someone always present in every meetings, but it depend on the individu in order to do not repeat the mistake that they have done so obviously giving a reward can motived the student in learning activity because the students will to compete to get that reward